Haemostatic Clot Formation at Anastomosis of Synthetic Venous Graft in Defibrinogenated Dogs: A Scanning Electron Microscopic Study - Ishimaru, S; Berglin, E; Hansson, H-A; Teger-Nilsson, A-C; William-Olsson, G (Thrombosis and Haemostasis, 1981)
A segment of the inferior vena cava was replaced by an expanded polytetrafluoroethylene graft in 13 dogs. Five of them served as a control group, while the other 8 were moderately or severely defibrinogenated with subcutaneous batroxobin. Plasma fibrinogen decreased to extremely low values throughout the experiment in the defibrinogenated dogs except in the moderately treated group in which it temporarily rose to 0.72-0.87 g/1 on the first postoperative day.Scanning electron microscopic observations of the haemostatic clot formed at the anastomoses of the graft revealed no significant morphological differences in platelet adhesion and/or aggregation between the three groups. These findings confirmed that platelets play a key role in primary haemostasis during defibrinogenation.The fibrin network was slightly diminished and only short fibrin filaments could be seen in the moderately and severely defibrinogenated groups respectively. These differences in composition of the clots are discussed in relation to their haemostatic capacity.
Keywords: Batroxobin; Defibrinogenation; Fibrin strands; Haemostasis; Platelet plug; Scanning electron microscopy